Tindakan Pilihan PAngan Ibu untuk Anak BALITA - Alawiyah, Silpa Dewi; Prasodjo, Nuraini Wahyuning (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2017)
In the last two years, the prevalence of underweight nutritional status in children under five years old, has increased nationally. This improved underweight nutritional status was assumed as the results of the food choice practice. The selection of the type of food consumed by children is generally determined by the mothers’ practice, which could be selecting the type of food. The purpose of this research is to analyze the relation between main motive of food choices and the practice of the mothers in choosing food.The method used in this research is  a survey method.. The results of this research are : 1) main  motive of mothers’ food choice in both village is not related to their practice of food choice, 2)the practice of mothers’ food choice in Cisarua Village is not related to nutritional status. However, in the village of Pasanggrahan the practice of food choice is related to nutritional status.Keywords: Motives of food choice, Food choice, Nutritional status-------------------------------------------------------------------------------------------ABSTRAKPrevalensi status gizi underweight pada anak balita secara nasional pada dua tahun terakhir mengalami peningkatan. Peningkatan status gizi underweight tersebut diduga salah satunya akibat tindakan pilihan pangan. Pilihan  jenis pangan yang dikonsumsi seorang anak umumnya ditentukan oleh tindakan ibu. Tindakan ibu tersebut dapat berupa menyeleksi jenis pangan. Penelitian ini bertujuan untuk menganalisis hubungan motif utama pilihan pangan dengan tindakan pilihan pangan oleh ibu. Metode yang digunakan pada penelitian ini adalah metode survei. Hasil dari penelitian ini adalah  motif utama pilihan pangan ibu di kedua desa tidak berhubungan dengan tindakan pilihan pangannya. Tindakan pilihan pangan  ibu di Desa Cisarua tidak berhubungan dengan status gizi, namun di Desa Pasanggrahan tindakan pilihan pangan berhubungan dengan status gizi.Kata Kunci : Motif utama pilihan pangan, Pilihan pangan, Status gizi